2022
DOI: 10.3390/nu14194080
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Impact of Zinc Supplementation on the Vascular Tissue of the Abdominal Aorta under Repeated Intoxication with Cadmium: A Study in an In Vivo Experimental Model

Abstract: In an in vivo rat model of human exposure to cadmium (Cd; 5 and 50 mg/L, 6 months), whether the supplementation with zinc (Zn; 30 and 60 mg/L, increasing its daily intake by 79% and 151%, respectively) protects against the unfavourable impact of this xenobiotic on the vascular tissue of the abdominal aorta was investigated. The treatment with Cd led to oxidative stress and increased the concentrations of pro-inflammatory interleukin 1β (IL-1β), total cholesterol (TC), triglycerides (TG), and endothelial nitric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Oxygen radicals are generated through the reduction of pathological alterations. Te ability of zinc to induce metallothionein (MT), which is crucial for defense against Cadmium toxicity, could reduce the harmful efects of oxygen radicals [25]. Immunohistochemical results indicated that the Bcl-2 expression was decreased in group's exposure to cadmium.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen radicals are generated through the reduction of pathological alterations. Te ability of zinc to induce metallothionein (MT), which is crucial for defense against Cadmium toxicity, could reduce the harmful efects of oxygen radicals [25]. Immunohistochemical results indicated that the Bcl-2 expression was decreased in group's exposure to cadmium.…”
Section: Discussionmentioning
confidence: 99%